Pengembangan Media Berbasis Hologram 3D Dalam Pembelajaran Tanaman Kelapa - Fauziah Eka Safitri; Djuniadi Djuniadi (JURNAL EKSAKTA PENDIDIKAN (JEP), 2021)
In recent years, the application and development of 3D hologram technology expanded in many areas, including to develop learning media. This research aimed at knowing the development, feasibility, effectiveness, practicability of usefulness and easiness of 3D hologram-based learning media on coconut plant theme lesson. The research has been carried out at kindergarten education with a sample of 24 students from TK Islam Al Madina Semarang. The method used is R&D with ADDIE development model, there are Analysis, Design, Development, Implementation, and Evaluation. The result reported that: the media 3D hologram for learning coconut plant has been developed by obtaining input from validator media and validator material, the developed media was considered feasible based on the media validator's assessment with score of 87% and the validator's material with a score of 80%, the developed media was effective, evidenced by mean score of post-test student's answers was 99,3, which is increase 24% compared to the pre-test 75; and the developed media was considered useful and easy to use by teacher and parents with their respective scores 82% and 92%. The overall result shows that the developed media hologram is feasible, effective, useful, and easy as a learning media.